(Non‐)donor demographics, donation willingness, and the donor career. Issue 6 (23rd March 2019) - Piersma, Tjeerd W.; Merz, Eva‐Maria
KEY IDEAS: Donation willingness is generally high but registering with donor centers lags behind. We need to understand why and when during the life course which groups of individuals are motivated to donate. With this knowledge, we can design targeted recruitment and retention strategies and improve evidence‐based donor management.